Four new species of Capsicum (Solanaceae) from the tropical Andes and an update on the phylogeny of the genus - Barboza, Gloria Estela (2019)
Four new species of Capsicum (Capsiceae, Solanaceae) from Andean tropical forests in outh America are described. Capsicum benoistii Hunz. ex Barboza sp. nov. (incertae sedis) is endemic to a restricted area in south-central Ecuador and is most similar to the more widespread C. geminifolium (Dammer) Hunz. (Colombia, Ecuador, and Peru). Capsicum piuranum Barboza & S. Leiva sp. nov. (Andean clade) is found in northern Peru (Department Piura) and is morphologically most similar to C. caballeroi M. Nee of the Bolivian yungas (Departments Santa Cruz and Cochabamba) but closely related to C. geminifolium and C. lycianthoides Bitter. Capsicum longifolium Barboza & S. Leiva sp. nov. (Andean clade) occurs from northern Peru (Departments Amazonas, Cajamarca, and Piura) to southern Ecuador (Province Zamora-Chinchipe), and is morphologically most similar to C. dimorphum (Miers) Kuntze (Colombia, Ecuador, and Peru). Capsicum neei Barboza & X. Reyes sp. nov. (Bolivian clade) is endemic to southeastern Bolivia (Departments Chuquisaca and Santa Cruz) in the Boliviano-Tucumano Forest, is morphologically most similar to another Bolivian endemic species C. minutiflorum Rusby (Hunz.), and is closely related to C. caballeroi. Complete descriptions, illustrations, distributions and conservation assessments of all new species are given. Chromosome numbers for C. piuranum and C. longifolium are also provided. Three of the new species were included in a new phylogenetic analysis for Capsicum; their positions were strongly resolved within clades previously recognized in the genus.